Properness and Topological Degree for Nonlocal Reaction-Diffusion Operators - N. Apreutesei; V. Volpert (Abstract and Applied Analysis)
The paper is devoted to integro-differential operators, which correspond to nonlocal reaction-diffusion equations considered on the whole axis. Their Fredholm property and properness will be proved. This will allow one to define the topological degree.